The promising novel therapies for familial hypercholesterolemia. Issue 7 (17th June 2022) - Chen, Ruoyu; Lin, Shaoyi; Chen, Xiaomin
Abstract: Background: The incidence of premature atherosclerotic cardiovascular disease in familial hypercholesterolemia (FH) is high. In recent years, novel therapeutic modalities have shown significant lipid‐lowering ability. In this paper, we summarize the recent developments in novel therapies for FH via the treatment of different targets and discuss the characteristics of each targeted therapy. Based on the process of protein synthesis, we attempt to summarize the direct‐effect targets including protein, RNA, and DNA. Methods: For this systematic review, relevant studies are assessed by searching in several databases including PubMed, Web of Science, Scopus, and Google Scholar. The publications of original researches are considered for screening. Results: Most drugs are protein‐targeted such as molecule‐based and monoclonal antibodies, including statins, ezetimibe, alirocumab, evolocumab, and evinacumab. Both antisense oligonucleotide (ASO) and small interfering RNA (siRNA) approaches, such as mipomersen, vupanorsen, inclisiran, and ARO‐ANG3, are designed to reduce the number of mRNA transcripts and then degrade proteins. DNA‐targeted therapies such as adeno‐associated virus or CRISPR–Cas9 modification could be used to deliver or edit genes to address a genetic deficiency and improve the related phenotype. Conclusion: While the therapies based on different targets including protein, RNA, and DNA are on different stages of development, the mechanisms of these novel therapies may provide new ideas for precision medicine. Abstract : The promising novel therapies for familial hypercholesterolemia.